Physical and anthropometric characteristics of youth volleyball players according to playing position and gender - Aytar, S. H. (International Journal of Applied Exercise Physiology, 2019)
The purpose of this study was to investigate some physical and anthropometric characteristics of youth volleyball players according to the playing positions and gender. A total of 562 volleyball players [308 female and 254 male] at the age of 14 were examined according to their playing positions [setter, spiker and middle blocker] in the study. Body height and weight and anthropometric measurements of the players were measured in order to determine body fat percentage, fat-free mass, sum of seven site skinfolds and somatotype of the players. According to the results, the difference between the genders was significant in all analyzed variables [p<0.05]. In terms of body fat percentage and somatotype except from the components of endomorphy and ectomorphy, the difference between the playing positions was significant in other physical and anthropometric characteristics [p<0.05]. In conclusion, it was possible to state that some physical and anthropometric characteristics were efficient on positioning in female and male volleyball players at the age of 14, and some anthropometric characteristics specific to the position could be gained by the training. Furthermore, results of this study provided normative data for the 14-year-old male and female volleyball players playing in specific individual positions.